Navigating tourism innovations in the post-COVID-19 era: A case study of Lithuania - Pociūtė-Sereikienė, Gintarė; Liutikas, Darius; Baranauskienė, Viktorija (Quaestiones Geographicae, 2024)
The goal of this article is to uncover the innovative changes that have emerged in Tourist Information Centres (TICs) in Lithuania as a result of the COVID-19 pandemic. The article is based on the assessment of primary research data collected through completed in-depth questionnaires. The research results revealed that a significant number of TICs transformed their activities while adapting them to local tourists. TICs introduced new products, attractions, and services, updated webpages and mobile applications, and created online souvenir shops. The research results indicated that, because of the lockdown, some state tourism institutions in the regions, along with local service providers, experienced a ‘renaissance’ and a successful period. New products and services were essential for the tourism sector’s survival, and the majority of them continue to be used in the post-COVID reality, providing opportunities for greater resilience and reduced dependence on unexpected circumstances in the future. This article addresses discussion points related to general changes in tourism services in the context of resilience and the application of innovations. Additionally, the article introduces the concept of Re-tourism, which adds value to the development of the theoretical framework for post-COVID tourism.